Analysis of Tax Avoidance and Tax Evasion Forms (Study on Taxpayers in the Trade Sector in Makassar City) - Susilo Haryanto (Journal of Entrepreneurship and Financial Technology, 2023)
In the trade sector, tax avoidance is developing into a complex and significant problem. The purpose of this study is to investigate the tax avoidance methods used by taxpayers working in the trade sector. This study analyzes various strategies and practices used by businesses to lower tax liabilities, including the use of tax avoidance and tax evasion methods. Data was collected through in-depth interviews with taxpayers from several trade subsectors, as well as document reviews and tax compliance data. Qualitative research methods were used to understand the reasons behind tax avoidance behavior and its impact on the state budget.The study shows that many taxpayers in the trade sector use tax avoidance methods to reduce fiscal burden. One way to avoid taxes is to use legal loopholes and tax incentives provided by the government to optimize business structures and reduce legitimate tax liabilities. Conversely, some businesses deliberately ignore tax obligations illegally. Tax avoidance in the trade sector has several consequences, such as a decrease in government revenue, which can hinder development and public services. In addition, this study shows how important awareness of corporate social responsibility and ethics is in the tax context. Efforts to improve and reform tax policies in the trade sector should consider the difficulties and opportunities to increase tax compliance and minimize tax evasion that is detrimental to society as a whole. So, to solve the problem of tax evasion in the trade sector, there needs to be a holistic approach that involves active participation from all parties involved, including the government, taxpayers, and society. Appropriate measures will bring sustainable economic and social progress through a fairer, more transparent and equitable tax system.